Relationship between emotional intelligence and job satisfaction among Texas instruments employees - Jamaluddin, Askiah; Gunaseelan, Arun; Mat Jusoh, Zuroni (2015)
The paper explores the relationship between emotional intelligence and job satisfaction among the employees of Texas Instruments. The emphasis will be on the distribution of respondents in terms of items in emotional intelligence and items in job satisfaction. This involves the explanation about the socioeconomic status of the respondents, the three types of emotional intelligence and job satisfaction. We also discuss the definition and the importance of emotional intelligence and job satisfaction in an organization. The research location is one of the established factories in Klang Valley, which is Texas Instruments. The results are explained based on the research objectives. The Pearson correlation analysis shows that there are significant relationships between emotional intelligence and job satisfaction among Texas Instrument employees. This paper aims to contribute information on emotional intelligence and job satisfaction to academicians, organizations and policy makers.